Notes on Occupational Classification - Alexandrin, Glen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1966)
In the first part of this article, the author shall attempt to sketch briefly the development of the « reality » of the labor force and of its « interpretative », descriptive concept — the occupational classification. In the second part, the analytical and policy tools of economies will be introduced.